Performance of Regional Government-Linked Companies in Indonesia: the influence of State Audit Board and regulations - Amdanata, Donal Devi; Noorhayati Mansor (Penerbit Universiti Kebangsaan Malaysia, 2020)
Regional Government-Linked Companies (RGLCs) in Indonesia have suffered from the unhealthy image and loss of respect from the public. The RGLCs are incapable of independently running the companies without financial support from the government. Accordingly, this research determines the effects of audits conducted by the State Audit Board of the Republic of Indonesia on the performance of RGLCs. This study also examines the influence of regulations on the RGLCs’. Agency theory and resource dependence theory provide the bases in developing the proposed hypotheses. The survey questionnaire was used to collect primary data. A total number of 57 out of 113 RGLCs (50.44%) made up the final sample. Each RGLC represented by six respondents, and the total final sample size was 342. The results provide new evidence that the financial audit does not affect the performance of RGLCs, while the Compliance audit indicates a positive effect on the performance of these RGLCs.